Attributes and constituent elements of the work process in Primary Health Care: experience report (Research, Society and Development, 2022)
Primary Health Care, also called Primary Care, is the main gateway and communication center with the entire Care Network in the Unified Health System. It should offer individual, family and collective health actions aimed at promotion, protection, diagnosis, treatment and rehabilitation, through a multidisciplinary team. Therefore, the objective of the study is to establish a theoretical-practical articulation between attributes, constituent elements of the work process and the reality of the service. This is an experience report, resulting from an activity linked to the practice of the Integration Program Teaching Service Community II module of the Medicine course, carried out in a Family Health Unit in a municipality in the western region of Paraná. For data collection, we used a previous form developed by the professors, based on the literature, in order to direct the activity according to the themes proposed for investigation. Based on the experiences analyzed, considerable advances were identified in the Brazilian health model. However, weaknesses were identified in health promotion actions and in the essential attributes of this care model. However, it is understood that through actions of permanent education and popular education in health, health work processes can be developed and improved in order to remedy the weaknesses identified.